KOSAKATA NGAYAM BELUNGKOR (PEMBUATAN TIKAR DARI DAUN LINGSING) BAHASA MELAYU DIALEK SAMBAS DI KECAMATAN SAMBAS - Fitriani, Nur; Patriantoro, Patriantoro; Jupitasari, Mellisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research was conducted by analyzing ngayam belungkor vocabulary of Sambas Dialect Malay Language in Sambas District with the aim to inventory and describe the form of lingual unit, lexical meaning, and function of ngayam belungkor vocabulary of Sambas Dialect Malay Language in Sambas District, as well as Indonesian language learning module on description text of class VII based on ngayam belungkor vocabulary of Sambas Dialect Malay Language in Sambas District. The method used is descriptive method with qualitative research form. The data source of this research is native speakers of Sambas Malay dialect who know ngayam belungkor activities. The data in this study are ngayam belungkor vocabulary in the form of words and phrases. The techniques used are observation, interview, recording, and note-taking techniques. The data collection tools used are questionnaires, stationery, and gadgets. Based on the results of the study, 60 data of ngayam belungkor vocabulary consisting of words (monomorphemic and polymorphic) and phrases were obtained, as well as Indonesian language learning modules in the form of description text.